Seismic fragility curves for old reinforced concrete building - Patil, V.S.; Tande, S.N. (Journal of Structural Engineering, 2024)
This paper discusses effect of ductile design and effect of loss of material strength due to age of construction on Probabilistic Seismic Demand Model (PSDM) of reinforced concrete (RC) frame. A three-storey three-bay moment resisting RC building situated in Mumbai which was designed to gravity loads and which lack in ductility provisions is taken for present study. This RC building is further modified by redesigning it to Indian seismic design code (IS1893-2002 Part I) and detailing as per IS13920-1993 Indian code to investigate variability in confinement of concrete in frame elements and hence ductility on the PSDM. Sixteen ground motion records are used to study the ground motion variability. Incremental dynamic analysis is performed on numerical model, and the maximum interstorey drift is obtained as a response parameter for all simulations. The PSDM parameters are calculated using regression analysis for old and modified building. The variation in the PSDM parameters is studied. Finally, the effects of ductile design and effect of loss of material strength due to age of construction on the seismic fragilities are discussed.